Survey-based assessment of the relationship between cognitive impairment and mentally stimulating activity in multiple sclerosis. (2nd September 2017) - Prager, Briana C.; Nowacki, Amy S.; Conway, Devon S.
Abstract: Objectives: Cognitive impairment (CI) is a common and potentially debilitating component of the disease course in multiple sclerosis (MS). However, therapeutic options remain limited. It is unknown whether cognitively enriching activities reduce the burden of CI in patients with MS, as is found in other neurologic diseases affecting cognition. The aim of this study was to determine whether participation in cognitively enriching activities decreased self-reported CI in MS patients. Methods: CI and activity levels were reported through electronic surveys completed by MS patients at the Cleveland Clinic. Responses were analyzed by univariable and multivariable regressions to identify factors associated with lower CI. Results: We received 316 survey responses. Use of an assistive device ( β = 4.09; P = 0.033) and Internet use ( β = 11.9; P = 0.017) were associated with higher reported CI, while employment correlated with reduced CI ( β = −7.97; P < 0.0001). None of the cognitive activities surveyed were found to reduce CI. Discussion: This study did not identify a significant impact of cognitively enriching activities on reducing CI, suggesting that other prophylactic or therapeutic approaches should be investigated. A small portion of the population surveyed reported no or minimal CI, suggesting the existence of a resilient population.